Low-Dose Everolimus Maintenance Therapy for Renal Angiomyolipoma Associated With Tuberous Sclerosis Complex - Luo, Cong; Ye, Wen-Rui; Zu, Xiong-Bin; Chen, Min-Feng; Qi, Lin; Li, Yang-Le; Cai, Yi (Frontiers in Medicine, 2021)
Purpose: To assess the safety and efficacy of low-dose everolimus maintenance therapy for tuberous sclerosis complex-related renal angiomyolipoma (TSC-RAML) patients that had previously undergone standard-dose treatment for a minimum of six months. Materials and Methods: In total, 24 patients with a definitive TSC diagnosis were enrolled from April 2018 – April 2019 at Xiangya Hospital, Central South University. All patients underwent low-dose everolimus maintenance therapy following standard-dose everolimus induction therapy for a minimum of 6 months. Patients additionally underwent TSC1/TSC2 genetic testing, and renal phenotypic analyses were performed after 3, 6, 12, 18, and 24 months. P < 0.05 was the significance level for all analyses, which were performed using SPSS 19.0. Results: TSC1/TSC2 gene mutations were present in all 24 patients, all of whom achieved a significant reduction in TSC-RAML volume within the initial 6-month induction therapy period, and exhibited volume stabilization during the low-dose maintenance therapy treatment period without any instances of TSC-RAML regrowth. Adverse events (AEs) were significantly less severe and less frequent over the course of maintenance therapy relative to standard therapy. Conclusions: Low-dose everolimus maintenance therapy represents an effective approach to achieving TSC-RAML control following a minimum of six months of full-dose induction therapy, and may be associated with decreases in everolimus-related AE frequency and severity.